2022
DOI: 10.3389/fimmu.2022.870531
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Machine Learning Model to Diagnose Chronic Autoimmune Diseases Utilizing Information From B Cells and Monocytes

Abstract: Heterogeneity and limited comprehension of chronic autoimmune disease pathophysiology cause accurate diagnosis a challenging process. With the increasing resources of single-cell sequencing data, a reasonable way could be found to address this issue. In our study, with the use of large-scale public single-cell RNA sequencing (scRNA-seq) data, analysis of dataset integration (3.1 × 105 PBMCs from fifteen SLE patients and eight healthy donors) and cellular cross talking (3.8 × 105 PBMCs from twenty-eight SLE pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Similarly, the random forest model used for a European SLE population based on the Gene Expression Omnibus (GEO) database showed an AUC of 0.776, which may be able to distinguish SLE patients from healthy individuals. Indeed, a study in another external cohort confirmed accuracy of the model in diagnosing SLE patients from healthy individuals with 100% sensitivity and 92.7% specificity 21 . Our prediction model for SLE patients with herpes obtained a higher AUC of 0.942, suggesting that the random forest model may be more valuable for clinicians to identify SLE patients with herpes.…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, the random forest model used for a European SLE population based on the Gene Expression Omnibus (GEO) database showed an AUC of 0.776, which may be able to distinguish SLE patients from healthy individuals. Indeed, a study in another external cohort confirmed accuracy of the model in diagnosing SLE patients from healthy individuals with 100% sensitivity and 92.7% specificity 21 . Our prediction model for SLE patients with herpes obtained a higher AUC of 0.942, suggesting that the random forest model may be more valuable for clinicians to identify SLE patients with herpes.…”
Section: Discussionmentioning
confidence: 56%
“…Applying machine learning algorithms to biomedicine largely promotes a better understanding and deconvolution of high-sequence information. Several studies have tried to decipher the heterogeneity of RA to some extent and have made limited advances in better understanding RA [ 33 , 36 ]. While the obsolete algorithm limited the reliability of clinical practice, a comprehensive understanding of RA in multiple cohorts with advanced machine learning algorithms is extremely urgent.…”
Section: Discussionmentioning
confidence: 99%
“… 127 128 Proteomics using cerebrospinal fluid demonstrated that CST6, L-selectin, Trappin-2, KLK5 and TCN2 could distinguish NPSLE from SLE controls (non-NPSLE). 124 Other reports using single-cell RNA sequencing data compared biomarkers for NPSLE to multiple sclerosis 103 and vascular dementia. 83 To differentiate cutaneous LE from other dermatological disorders such as psoriasis, eczema, atopic dermatitis and systemic sclerosis (RF model, AUC 0.774–0.990), interferon gene signature, tumour necrosis factor, interleukin-23 (IL-23), interferon (IFN), IL-12, and immune cell-related genetic signatures were selected as important biomarkers.…”
Section: Key Sle Findings By ML Reportsmentioning
confidence: 99%